PENGARUH KOMPETENSI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. KARYA MURNI PERKASA - Herry Ginting Suka; Tanta Bina Barus; Nadela Veronika Ginting; Try Cyntia Gultom (JURNAL ILMIAH SOCIO SECRETUM, 2021)
This study aimed at determining and analyzing the influence of competence and work stress on employees’ performance. The competency phenomenon in PT. Murni Murni Perkasa is lack of employees’ performance that was not good because of the incompatibility of the educational background in the field which resulted in many employees not working optimally. The work stress phenomenon in PT Karya Murni Perkasa was caused by too high job demand which influenced performance and caused the high level of resignation at the company. The research method used was quantitative approach. The type of research was descriptive quantitative and the nature of this research was descriptive explanatory. The data collection was done by interviews and questionnaires. The analytical method used was multiple linear regression analysis. The population used in this study was employees at PT. Karya Murni Perkasa. Determination of samples in this study was done by using simple random sampling, so that the sample used amounted to 101 people. The results showed that work competence and stress had a significant effect on employees’ performance at PT Karya Murni Perkasa. The results of the analysis of the factors influencing employees’ performance showed that between the two variables analyzed, the most dominant influence on employee performance was the work stress variable. This was proved by the results of the calculation of each variable (t test), which was the t test on work stress. The conclusions in this study were that competency and work stress variables rejected H0 and accepted H1. Thus it was partially showed that job competence and stress had a positive and significant effect on employees’ performance at PT Karya Murni Perkasa. Simultaneously the performance and competency variables had a positive and significant effect on employees’ performance.